Analysis of Factors Affecting the Value of Indonesian Crude Palm Oil (CPO) Exports to the United States When the RFS Policy is in Effect - Putra Fajar Maulana; Sishadiyati (Cita konsultindo, 2025)
The Renewable Fuel Standard (RFS) policy in the United States presents both opportunities and challenges for Indonesia’s Crude Palm Oil (CPO) exports. This study aims to analyze the factors influencing the value of Indonesia’s CPO exports to the United States during the period 2005–2023, focusing on Malaysia’s export volume, Indonesia’s CPO production, and international CPO prices. A quantitative method with time series data was employed and analyzed through multiple linear regression using EViews 13. The results show that Malaysia’s CPO export volume has a negative and significant effect on Indonesia’s export value, indicating direct market competition. In contrast, Indonesia’s CPO production has a positive and significant effect, underscoring the importance of domestic capacity in supporting export performance. International CPO prices also have a positive and significant effect, meaning that rising global prices can increase export value. Overall, the findings confirm that beyond demand and supply dynamics, competition with Malaysia and compliance with the RFS standard are crucial determinants of export performance. This study recommends strengthening sustainability certification (ISPO), enhancing trade diplomacy, and stabilizing production to improve competitiveness in the U.S. market.